2012
DOI: 10.1097/igc.0b013e318244248c
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Versus Abdominal Approach to Endometrial Cancer: A 10-Year Retrospective Multicenter Analysis

Abstract: Objective: The objective of this study was to give a reality-based picture of the use of laparoscopic surgery for staging endometrial cancer patients out of the experimental setting. Methods: Consecutive data of patients with endometrial cancer who underwent laparoscopic or abdominal surgical staging in 6 Italian centers were recorded. Baseline patients and tumors characteristics, surgery performed, and safety data were collected and analyzed. Results: A total of 1012 subjects (403 and 609 treated by laparosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 25 publications
(11 reference statements)
5
16
0
1
Order By: Relevance
“…The effect of surgical stage on the conversion rate is here well documented. In fact, the proportion of patients with endometrial cancers at stages higher than I was significantly higher in converted patients than in laparoscopy patients conforming the high conversion rate in advanced stage endometrial cancers and that the feasibility of the laparoscopy for treating endometrial cancers is optimal for early stages alone [5].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…The effect of surgical stage on the conversion rate is here well documented. In fact, the proportion of patients with endometrial cancers at stages higher than I was significantly higher in converted patients than in laparoscopy patients conforming the high conversion rate in advanced stage endometrial cancers and that the feasibility of the laparoscopy for treating endometrial cancers is optimal for early stages alone [5].…”
Section: Discussionmentioning
confidence: 95%
“…In a wide retrospective analysis of 1,012 subjects who received surgical staging for endometrial cancer in different surgical settings, the safety and the feasibility of laparoscopic staging was confirmed for stage I endometrial cancers [5], and seemed highly feasible and quite safe in stage II endometrial cancers as well [5]. Instead, it should be used with caution in patients with stages III or IV endometrial cancers [5].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Although several studies [14,19,20] have suggested that the grade of the tumor and the histological type could draw the indication for the surgical approach. In our study, the surgical approach was not influenced by the grade of the tumor.…”
Section: Discussionmentioning
confidence: 99%